BIX-01294 promotes the differentiation of adipose mesenchymal stem cells into adipocytes and neural cells in Arbas Cashmere goats. (August 2018) - Wang, Qing; Wang, Xiao; Lai, Defang; Deng, Jin; Hou, Zhuang; Liang, Hao; Liu, Dongjun
Abstract: Chromatin remodeling plays an essential role in regulating gene transcription. BIX-01294 is a specific inhibitor of histone methyltransferase G9a, which is responsible for methylation of histone H3 lysine 9 (H3K9) that can also regulate DNA methylation and chromatin remodeling. The purpose of this study was to investigate the effects of BIX-01294 on the potential of goat adipose derived stem cells (gADSCs) to differentiate into adipocytes and neural cells. To accomplish this, BIX-01294 was used to treat gADSCs for 24 h, and the global level of DNA methylation as well as the expression of genes related to cell proliferation, apoptosis and pluripotency were detected. At the same time, the cells were induced to differentiate into adipocytes and neural cells, and the transcription levels of related marker factors were examined. We found that BIX-01294 treatment reduced the level of DNA methylation and increased the level of gADSCs hydroxylmethylation. The translation level of NANOG increased, whereas Oct4, Sox2 levels decreased. Our results suggest that BIX-01294 may rely on the NANOG regulatory network to promote gADSCs differentiation. We found that both the lipid droplet level in adipocytes and the transcription levels of the adipocyte specific factors Fabp4, ADIPOQ, and Leptin increased after treatment. ENO2 and RBFOX3 transcription levels were also elevated in the differentiated neural cells after treatment. These results indicated that BIX-01294 treatment promoted the differentiation of gADSCs into adipocytes and neural cells. Our findings provide new ideas for improving the differentiation potential of gADSCs and expanding possible application for gADSCs. Highlights: BIX-01294 is a specific inhibitor of histone methyltransferase G9a. BIX-01294 reduced global DNA methylation and increased gADSC hydroxylmethylation. BIX-01294 increased the mRNA levels of adipocyte-specific factors. BIX-01294 promoted the differentiation of gADSCs into adipocytes and neural cells. BIX-01294-mediated differentiation process involved the NANOG regulatory network.